Pengaruh psychological well being dan work life balance terhadap job performance melalui work engagement pada perawat Z generation Rumah Sakit Umum Anwar Medika - Zafirah, Ainun Is Yuni; Budiono (Universitas Negeri Surabaya, 2024)
This research aims to determine and explain the effect of psychological well-being and work-life balance on job performance through work engagement in Z-generation nurses at a private hospital in Sidoarjo Regency. This research is classified as quantitative research with a population of 116 nurses belonging to Generation Z, and the sampling technique used proportionate stratified random sampling with a total sample of 90 Generation Z nurses. The statistical analysis used in this research was Structural Equation Modeling (SEM) with the help of Smart software Partial Least Squares (PLS) 3.2.9. The results of this research show that psychological well-being has a significant positive effect on work engagement, work-life balance has a considerable positive impact on work engagement, work engagement does not affect job performance, psychological well-being has a significant positive effect on job performance, work-life balance does not affect job performance, work engagement cannot mediate the influence of psychological well-being on job performance, work engagement cannot mediate the impact of work-life balance on job performance. The implications are based on the results applied to companies where superiors can organize decision-making training programs for Generation Z nurses and hold individual counseling and coaching sessions as a skill development path for employee orientation mentoring programs. Apart from that, superiors can also monitor employee satisfaction to provide opportunities for employees to be involved in decision-making.